2003
DOI: 10.1152/ajpendo.00117.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver in type 2 diabetes mellitus: relation to regional adiposity, fatty acids, and insulin resistance

Abstract: . Fatty liver in type 2 diabetes mellitus: relation to regional adiposity, fatty acids, and insulin resistance. Am J Physiol Endocrinol Metab 285: E906-E916, 2003; 10.1152/ajpendo.00117.2003.-The current study was undertaken to examine metabolic and body composition correlates of fatty liver in type 2 diabetes mellitus (DM). Eighty-three men and women with type 2 DM [mean body mass index (BMI): 34 Ϯ 0.5 kg/m 2 ] and without clinical or laboratory evidence of liver dysfunction had body composition assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
294
7
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(336 citation statements)
references
References 49 publications
27
294
7
5
Order By: Relevance
“…Among the non-diabetic subjects, serum CRP was significantly correlated with the VFA in subjects with BMI≥25, but not in those with BMI<25; there was no significant correlation between serum CRP with L/S ratio or SFA in the non-diabetic subjects, irrespective of BMI. Thus, serum CRP showed no significant correlation with VFA and SFA in the nonobese subjects (BMI<25) ( Table 3), consistent with previous reports [7,17].…”
Section: Resultssupporting
confidence: 91%
“…Among the non-diabetic subjects, serum CRP was significantly correlated with the VFA in subjects with BMI≥25, but not in those with BMI<25; there was no significant correlation between serum CRP with L/S ratio or SFA in the non-diabetic subjects, irrespective of BMI. Thus, serum CRP showed no significant correlation with VFA and SFA in the nonobese subjects (BMI<25) ( Table 3), consistent with previous reports [7,17].…”
Section: Resultssupporting
confidence: 91%
“…In agreement with the hypothesis that ectopic fat accumulation may be related to impaired insulin action, an increased IMCL content in association with peripheral insulin resistance was reported in patients with type 1 diabetes as well as in patients with type 2 diabetes and their relatives [4]. More recently it was suggested that ectopic fat accumulation within the liver may be also associated with peripheral and hepatic insulin resistance in nondiabetic individuals [5,6] and is common in obese patients with type 2 diabetes [20]. Some authors suggest that fatty liver represents a body composition manifestation of obesity and visceral adiposity in insulin-resistant subjects [21], but at the same time they suggest that the impact on insulin sensitivity is determined regardless of intra-abdominal and overall adiposity [6].…”
Section: Discussionsupporting
confidence: 73%
“…Since hepatic insulin resistance was significantly related to liver fat content independently of BMI, subcutaneous fat volume and intra-abdominal fat volume (as assessed by MRI), the authors concluded that hepatic steatosis rather than adipose tissue triglyceride content can be a major determinant of insulin resistance in humans. Kelly et al [46] recently reported that the presence of liver steatosis (assessed using computerised tomography criteria) in patients with type 2 diabetes is associated with more severe insulin resistance (during a 6 pmol min −1 kg −1 insulin clamp). Using both a low-dose (1.5 pmol min −1 kg −1 ) and a high-dose (6 pmol min −1 kg −1 ) insulin infusion, we have conclusively demonstrated the co-existence of hepatic and peripheral insulin resistance in biopsy-proven NAFLD independent of obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%